Mercados culturais no Brasil: a expansão dos shoppings centers e das livrarias megastores - Carlos Alexsandro de Carvalho Souza (Ciências Sociais Unisinos)
This work presents some of the most recent transformations in the relations between culture and market in contemporary Brazil, in order to indicate some of the empirical indicators that have been able to reshape and resize the strategies of some of the main market agents involved in this process, whether state or private, generating all sorts of new business models and companies classified as cultural, inscribed in the widespread expansion of the entertainment and leisure markets. It should be noted that the reflections are included on what part of the specialized literature in the social sciences categorizes as creative economy, specially due to the management of the agents involved, of the new aesthetic and symbolic justifications that start to develop a panorama which, based on the general growth of the Brazilian economy in the period considered, indicates the robustness of what can be described as contemporary cultural capitalism. The work takes as its object a very specific business model, chosen to problematize the convergence of the relationships highlighted above and its potential to better distribute new habits of consumption: bookstores with the megastore model that, as the investigations pointed out, represent one of the most abundant model in today’s cultural markets. Its relationship with shopping malls, as will be seen, was a fundamental condition for its expansion and commercial success and, at least discursively, in the construction of a self-image as a cultural equipment.